A Three‐Site Mechanism for Agonist/Antagonist Selective Binding to Vasopressin Receptors. (13th May 2016) - Saleh, Noureldin; Saladino, Giorgio; Gervasio, Francesco L.; Haensele, Elke; Banting, Lee; Whitley, David C.; Sopkova‐de Oliveira Santos, Jana; Bureau, Ronan; Clark, Timothy
Abstract: Molecular‐dynamics simulations with metadynamics enhanced sampling reveal three distinct binding sites for arginine vasopressin (AVP) within its V2 ‐receptor (V2 R). Two of these, the vestibule and intermediate sites, block (antagonize) the receptor, and the third is the orthosteric activation (agonist) site. The contacts found for the orthosteric site satisfy all the requirements deduced from mutagenesis experiments. Metadynamics simulations for V2 R and its V1a R‐analog give an excellent correlation with experimental binding free energies by assuming that the most stable binding site in the simulations corresponds to the experimental binding free energy in each case. The resulting three‐site mechanism separates agonists from antagonists and explains subtype selectivity.